MULTICULTURAL ISLAMIC EDUCATION LEARNING SYSTEM - Makrufi, Anisa Dwi; Tumin, Tumin; Hasan, Yusuf Abdul (State Islamic University of Datokarama Palu, 2021)
This article aims to discuss the implementation of multicultural education through religious education in schools, especially in the digital era. To reach this research, the relevant literature has been carried out. As a result, Islamic Education is a forum to provide a religious understanding that is inclusive of the community which is ultimately expected to contribute to the formation of a multicultural society with a harmonious life. Multicultural education involves at least three things, namely: a) ideas and awareness of the importance of cultural diversity, b) educational reform movement, and c) process. The learning system of Islamic Education that has multicultural insight should be done by integrating multicultural insights with existing Islamic Education material. The involvement of principals and the government is also needed in providing debriefing or training and the like. The method used must also be packaged in such a way as to condition students to interact with each other in harmony. Likewise, the evaluation process carried out must be based on the principle of fairness objectively rather than subjective certain groups.